Bestlink College of the Philippines Bachelor of Library and Information Science: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In the digital age, academic libraries face several challenges, such as budget constraints, adapting to new technology, changes in research and teaching, and internal and external settings. Effective marketing can assist libraries in addressing these issues. Libraries must market their services and resources effectively to attract clients, raise awareness of available resources, and generate non-user awareness. With the advancement of science and technology, libraries are using ICT-based marketing strategies to increase usage. This chapter examines how academic libraries, especially those in higher education institutions, can use marketing tactics to maximize the use of library resources to satisfy their users. The study aims to evaluate the marketing strategies used in Bestlink College of the Philippines' academic library. Performance measurement assesses if libraries and information services are functioning efficiently and effectively. The library offers various information materials to support the institution's academic needs. The research aims to improve the library services of Bestlink College of the Philippines by evaluating the marketing strategy used by the BCP Academic Library. The researchers used a descriptive research method with both qualitative and quantitative methodologies, including self-made questionnaires, unstructured interviews, group discussions, and documentary analysis. The respondents were from the thirteen courses regulated by the Profession Regulatory Commission (PRC) at Bestlink College of the Philippines. While students are satisfied with the library collection's substance, the findings indicate that respondents are not satisfied with the library collection.Add Contributor